The Effectiveness of Resilient Dialectical Behavior Therapy and Dialectical Behavior Therapy on Coping Strategies and Resilience in Women Experiencing Marital Burnout - Maryam Shirani Nazhvani; Felor Khayatan; Hadi Farhadi (Women’s Health Bulletin)
Background: Marital burnout significantly affects many women, leading to emotional distress and decreased quality of life. The present study aimed to investigate the effectiveness of resilient dialectical behavior therapy (RDBT) and dialectical behavior therapy (DBT) on improving coping strategies and resilience in women experiencing marital burnout.Methods: This quasi-experimental study employed a pre-test, post-test, and two-month follow-up design to evaluate the efficacy of Dialectical Behavior Therapy (DBT) and Relational Dialectical Behavior Therapy (RDBT) in addressing marital burnout among women aged 25-50. The study participants were recruited from counseling centers in Isfahan, Iran, during the Spring of 2023. A convenience sample of 45 women was randomly allocated to three groups: DBT (n=15), RDBT (n=15), and a control group (n=15). The experimental groups received nine weekly, 60-minute therapy sessions, while the control group received no intervention. The Coping Inventory for Stressful Situations (CISS) and Connor-Davidson Resilience Scale (CD-RISC) were administered at pre-test, post-test, and follow-up. Repeated measures ANOVA and Bonferroni post-hoc tests were used to analyze the data, which was processed using SPSS version 27.Results: Both interventions had a significant positive effect on improving coping strategies and resilience in women experiencing marital burnout (P<0.001). At post-test, the RDBT group demonstrated significantly higher levels of problem-focused coping than the DBT group, with mean scores of 16.80 (95% CI: 14.43, 19.17) and 7.20 (95% CI: 4.83, 9.57), respectively. Both groups exhibited decreases in emotion-focused coping, with the RDBT group showing a more pronounced decline (-10.47, 95% CI: -12.83, -8.11) compared with the DBT group (-6.54, 95% CI: -8.91, -4.17). Similarly, the RDBT group demonstrated a greater reduction in avoidant coping (-11.13, 95% CI: -13.59, -8.67) compared with the DBT group (-7.93, 95% CI: -10.3, -5.56). Finally, both groups exhibited significant increases in resilience, with the RDBT group showing slightly higher levels at post-test (33.13, 95% CI: 30.77, 35.49) compared with the DBT group (31.14, 95% CI: 28.77, 33.51).Conclusions: The findings of this study demonstrate the efficacy of both DBT and RDBT in enhancing coping strategies and resilience among women experiencing marital burnout. These results underscore the potential of DBT and RDBT in addressing the psychological challenges associated with marital distress.